2016
DOI: 10.2131/jts.41.711
|View full text |Cite
|
Sign up to set email alerts
|

Adverse health effects of humidifier disinfectants in Korea: lung toxicity of polyhexamethylene guanidine phosphate

Abstract: -Exposure to humidifier disinfectants was identified in 2011 as the potential cause of an outbreak of lung disease in Korea. It is estimated that over 8 million people have been exposed to humidifier disinfectants-chemicals added to the water used in humidifiers to prevent the growth of microorganisms-since their commercial introduction. The primary component of humidifier disinfectant products involved was polyhexamethylene guanidine phosphate (PHMG-P), a guanidine-based antimicrobial agent. Lesions observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 25 publications
(28 reference statements)
1
27
0
1
Order By: Relevance
“…Polyhexamethylene guanidine (PHMG) is a guanidine-based polymeric antimicrobial agent [11][12][13]. The major two derivatives of its salt, PHMG phosphate (PHMG-p) and PHMG hydrochloride, are widely used in detergents, paints, and swimming pools [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Polyhexamethylene guanidine (PHMG) is a guanidine-based polymeric antimicrobial agent [11][12][13]. The major two derivatives of its salt, PHMG phosphate (PHMG-p) and PHMG hydrochloride, are widely used in detergents, paints, and swimming pools [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The cytokine-mediated inflammatory response is considered to play a crucial role in the progression of PHMGinduced pulmonary fibrosis (Kim et al, 2016(Kim et al, , 2018. Therefore, the exploration of the regulatory mechanisms underlying the inflammatory response is important to elucidate the mechanism of PHMG-induced lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that the inflammatory response induced by PHMG is significantly associated with the development of pulmonary fibrosis (Song et al, 2014;Kim et al, 2016Kim et al, , 2018. Cytokines, which are proteins secreted by all kinds of cells, act as fundamental mediators between cells (Lacy and Stow, 2011;Arango Dugue and Descoteaux, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The latter seems to be more probable as PHMG has no strong hepatotoxicity; its LD50, when administered orally, has been around 450 mg/kg for mice and 630 mg/kg for rats (Lachenmeier et al ., 2012) or somewhat higher, while the animals died with signs of injury to the nervous system (Asiedu-Gyekye et al ., 2014, 2015; Kondrashov, 1992; Tsisanova & Salomatin, 2010). Lung lesions due to PHMG used in household humidifiers have been reported (Kim et al ., 2016), but no reports on liver injury in humans have come to our attention.…”
mentioning
confidence: 99%
“…The difference between LD50 estimates in rats for PHMG and PHMB by the same researchers in two consecutive studies was striking: 600 vs. 25.6 mg/kg (Asiedu-Gyekye et al ., 2014, 2015). Note that general toxicity of both substances is largely similar with LD50 values 500-600 mg/kg in rats when administered orally (Kim et al ., 2016). The question is whether the value 25.6 mg/kg (Asiedu-Gyekye et al ., 2015) could have resulted from added precaution due to information on the mass poisoning in Russia (Ostapenko et al ., 2011) cited by Asiedu-Gyekye et al .…”
mentioning
confidence: 99%